2022
DOI: 10.1097/cce.0000000000000743
|View full text |Cite
|
Sign up to set email alerts
|

Baseline Anxiety and Depression and Risk for ICU Delirium: A Prospective Cohort Study

Abstract: OBJECTIVES: Anxiety and depression are common mental disorders in adults admitted to the ICU. Although depression increases postsurgical delirium and anxiety does not, their associations with ICU delirium in critically ill adults remain unclear. We evaluated the association between ICU baseline anxiety and depression and ICU delirium occurrence.DESIGN: Subgroup analysis of a prospective cohort study. SETTING: Single, 36-bed mixed ICU.PATIENTS: Nine-hundred ninety-one ICU patients admitted with or without delir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Brain metastases, signifying invasion of the central nervous system, directly affect brain function, increasing the likelihood of delirium [36]. Mental and emotional state factors highlight the psychological health of patients, with anxiety and depression assessed by SAS and SDS scores, respectively, marking critical concerns for advanced cancer patients facing end-of-life distress [37]. These psychological aspects not only affect mental health but can also impair cognitive function and increase the risk of delirium [38].…”
Section: Discussionmentioning
confidence: 99%
“…Brain metastases, signifying invasion of the central nervous system, directly affect brain function, increasing the likelihood of delirium [36]. Mental and emotional state factors highlight the psychological health of patients, with anxiety and depression assessed by SAS and SDS scores, respectively, marking critical concerns for advanced cancer patients facing end-of-life distress [37]. These psychological aspects not only affect mental health but can also impair cognitive function and increase the risk of delirium [38].…”
Section: Discussionmentioning
confidence: 99%
“…Again, the relationship between the underlying disease state (i.e., hypertension, either controlled or uncontrolled), effective medication therapy, and delirium warrants further exploration. While baseline anxiety and depression are known strong risk factors for the development of delirium, a secondary analysis of the BRAIN‐ICU study recently demonstrated that the use of selective serotonin reuptake inhibitors (SSRIs) was associated with a decreased risk of delirium and coma 36,37 . These findings warrant further exploration to determine the association between baseline mental illness, effective chronic treatment (i.e., SSRI therapy) versus new initiation during critical illness, and subsequent impact on delirium.…”
Section: Select Medications That May Impact Icu Deliriummentioning
confidence: 99%
“…for the development of delirium, a secondary analysis of the BRAIN-ICU study recently demonstrated that the use of selective serotonin reuptake inhibitors (SSRIs) was associated with a decreased risk of delirium and coma. 36,37 These findings warrant further exploration to determine the association between baseline mental illness, effective chronic treatment (i.e., SSRI therapy) versus new initiation during critical illness, and subsequent impact on delirium.…”
Section: While Baseline Anxiety and Depression Are Known Strong Risk ...mentioning
confidence: 99%
“… 4 , 6 , 7 , 8 , 9 , 10 However, our understanding of potentially modifiable risk factors for dementia after ICU hospitalization is limited. Cardiovascular risk factors and depression 11 , 12 occur commonly in older ICU survivors and are well‐established, potentially modifiable risk factors for dementia. 13 , 14 , 15 , 16 , 17 Whether these risk factors are also associated with post‐ICU dementia have not been clearly established.…”
Section: Introductionmentioning
confidence: 99%